2021
DOI: 10.3390/cancers13174449
|View full text |Cite
|
Sign up to set email alerts
|

A Truncated NRIP1 Mutant Amplifies Microsatellite Instability of Colorectal Cancer by Regulating MSH2/MSH6 Expression, and Is a Prognostic Marker of Stage III Tumors

Abstract: Microsatellite instability (MSI) is related to the alteration of mismatch repair (MMR) genes and plays a key role in colorectal cancer (CRC) pathogenesis. We previously reported that the transcription factor Nuclear Receptor Interacting Protein 1 (NRIP1) is involved in sporadic intestinal tumorigenesis. The aim of this study was to decipher its role in MSI CRC. By using different mouse models and engineered cell lines, we demonstrated that NRIP1 increased MSH2 and MSH6 MMR gene transcription and mRNA/protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 50 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…We recently demonstrated that RIP140 plays an important role in controlling microsatellite instability through the regulation of MSH2 and MSH6 genes [ 26 ] . To compare the correlation between RIP140 and POLK gene expression in microsatellite stable (MSS) and instable (MSI) CRC tumors, we reanalyzed a transcriptomic dataset from 396 human CRC with both types of tumors [ 34 ] .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently demonstrated that RIP140 plays an important role in controlling microsatellite instability through the regulation of MSH2 and MSH6 genes [ 26 ] . To compare the correlation between RIP140 and POLK gene expression in microsatellite stable (MSS) and instable (MSI) CRC tumors, we reanalyzed a transcriptomic dataset from 396 human CRC with both types of tumors [ 34 ] .…”
Section: Resultsmentioning
confidence: 99%
“…In MSI CRC, we identified a frameshift mutation in the RIP140 coding sequence [ 26 ] . This mutation (called RIP MSI ) generated a truncated protein which impaired the biological activity of the RIP140 protein.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations